2001
DOI: 10.1093/brief-treatment/1.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Focused Single‐Session Psychotherapy: A Review of the Clinical and Research Literature

Abstract: Since the initial examination of the scattered literature on single-session psychotherapy, more than 40 papers that address some aspect of this form of very brief psychotherapy have been located in two archival data sets (PsycINFO and MEDLINE). The literature consists of clinical overviews, program descriptions and case presentations, and a few uncontrolled and controlled outcome studies. Single-session psychotherapy has been practiced from a wide variety of theoretical perspectives with no evidence thus far t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 32 publications
2
72
0
3
Order By: Relevance
“…Significant improvement in severity and frequency of presenting problem for the treatment group was reported compared to the control after 6 weeks. Reviews of these studies have concluded that SST may be helpful for some clients, but more rigorous research is needed (Bloom, 2001;Cameron, 2007;Campbell, 2012;authors, 2013;Hurn, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvement in severity and frequency of presenting problem for the treatment group was reported compared to the control after 6 weeks. Reviews of these studies have concluded that SST may be helpful for some clients, but more rigorous research is needed (Bloom, 2001;Cameron, 2007;Campbell, 2012;authors, 2013;Hurn, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several descriptive reviews of SST and walk-in SST have concluded that while more experimental research is required in the area, these single-session approaches appear to be effective for a range of problems and can satisfy client expectations (Bloom, 2001;Cameron, 2007;Campbell, 2012;Hymmen et al, 2013). Although the use of a consultancy team is not a universal feature of all single-session therapeutic methods, like other brief methods (e.g., de Shazer, 1985;Selvini & Palazzoli, 1991), it is a characteristic of therapy that is commonplace to the majority of these approaches.…”
Section: Consultancy Teams In Single-session Therapymentioning
confidence: 99%
“…They are also able to see more clients in a short period of time. Walk-in services thus fall into the category of brief interventions, which have consistently been shown to be effective (Bloom, 2001).…”
Section: Walk-in Counseling Servicesmentioning
confidence: 99%